Family Supporting on Quality of Life among Children with Cancer in Women and Children Harapan Kita Hospital, Jakarta - Sari, Widia; Azzah, Fhasa Lifiansah; Pamungkas, Rian Adi; Rosya, Ernalinda; Asmirajanti, Mira; Handayani, Eka; Antoni, Antoni (Alta Dharma Publisher, 2023)
Background: The prevalence of cancer is continuously increasing every year. Cancer treatment has a long duration, that side effects in children impact their quality of life. Therefore, family support is needed to improve the quality of life in children. Objective: This study aimed to find a correlation between supporting the family on the quality of life of children with cancer. Method: The method of this study was a cohort study with seven days of follow-up of the respondent. The sample accounted for 28 children hospitalized in Anggrek Ward and Outpatient Hemato-Oncology from June-August 2022 and collected data using PedsQL 4.0 Generic Core Scales Questionnaire and family support questionnaire. Result: The result was a significant correlation between family support and quality of life in children with cancer during seven days of follow-up (p<0.005) with a positive correlation. This study also found that the social function had a higher and lower mean value than the school function. Conclusion: The higher the family support, the better the quality of life for children. Recommendation: the family is always expected to attend to the child during the hospital, hospice, or home treatment